Determination of Water Content in Dehydrated Mammalian Cells Using Terahertz Pulsed Imaging: A Feasibility Study - Y.S. Chau, David; R Dennis, Anthony; Lin, Hungyen; Axel Zeitler, J.; Tunnacliffe, Alan (Current Pharmaceutical Biotechnology, 2016)
Mammalian cells are involved in a range of biotechnological applications and more recently have been increasingly exploited in regenerative medicine. Critical to successful applications involving mammalian cells are their long-term storage and transport, for which cryopreservation in liquid nitrogen is the most frequently used strategy. However, cryopreservation suffers from high costs, difficulties in transport logistics and the use of undesirable additives (e.g. animal sera or DMSO). An alternative approach, proposed as low cost, low maintenance and process-compatible, is viable desiccation of mammalian cells. Several groups claim to have achieved this, but the extent of desiccation in the cell samples concerned is not always clear, in part because of difficulties in determining very low water content. Although several techniques exist that are frequently used to quantify the amount of water in samples (e.g. FTIR spectroscopy, thermogravimetric analysis (TGA), NMR spectroscopy), the complexity of sample preparation, as well as the costs and time constraints involved are disadvantageous. Here, we assess a novel, rapid and low cost technique, i.e. terahertz (THz) spectroscopy, for the quantification of water content within dehydrated mammalian cell samples.
Keywords: desiccation